Diversity and Distribution Patterns of Gastropods on Kupang Beach, Seruway District - Halimatun, Futria; Mawardi, Abdul Latif; Wahyuni, Ayu; Hariani, Indri; Fauziah, Cut (Jurnal Biologi Tropis, 2024)
Seruway is one of the sub-districts in Aceh Tamiang, which is located in the coastal area. This coastal area is dominated by mangrove species, where the mangrove area is used as a habitat for aquatic biota animals, one of which is gastropods. Gastropods are soft-bodied animals that have threaded shells. This research aims to determine the value of the species diversity index and distribution patterns of gastropods in Kupang Beach, Seruway District. This research is a type of quantitative descriptive research with sampling using a survey method. Sampling was taken using transects. Sampling was divided into 3 stations, namely the first station in the mangrove area, the second station in the beach area and the third station in the pond area. Each station consists of 4 transects measuring 50 meters, each transect has 4 plots measuring 10x10m. Samples that are obtained will be identified using an identification book. The research results showed that the number of gastropod species found was 17 species from 9 families with a total diversity index value at the research location, namely H'= 2.405, which is classified as medium. The distribution pattern of gastropods on Kupang Beach falls into two categories, namely the uniform category 59% and the undefined category 41%.